Priporočila za uporabo različnih biotehniških metod in kemičnih sredstev za obvladovanje podlubnikov (Curculionidae: Scolytinae) - Jurc, Maja (Gozdarski vestnik, 2017)
In the last decades in Slovenia numerous extreme weather phenomena take place; among them, the worst dimensions and consequences had the hundred year drought in 2003 and icestorm (sleet) in February 2014. The climatologists forecast droughts and major disasters also for the future. They will cause major mechanical and physiological damage of forest trees. Above all in the lowland stand of the Norway spruce (Picea abies) we can also expect major damages due to biotic factors, e.g. Ips typographus, Pityogenes chalcographus and other bark beetles, native phytoparasites and invasive non-native harmful organisms. In the field of integrated forest protection (IFP) we stand in front of new professional challenges of the application of new knowledge on abiotic and biotic forest damages in Slovenia and abroad, fast changes of weather conditions in environment, and increasing entry of non-native harmful species into the forests. These facts require development and application of modern IFP strategies (MSIFP). In this article we deal with an important segment of IFP: adequacy of diverse biotechnical methods and chemical agent application for bark beetle control. Bark beetles infestation requires performing all integrated forest protection actions. Preferentially and all year round sanitation felling of the bark beetle infested spruce trees and removal of infested trees from the forest, followed by destruction of bark beetles. Extremely important is timeliness of performance of these actions; it must take place before flying out of a new beetle generation, which requires appropriate technical support, coordination, and good organization of all actors of these actions. As an additional action for bark beetle damage reduction it makes sense to increase the number of pheromone traps and "trap trees" in form of fallen trees, trunks and piles (with the thicker parts of branches on the outside of the pile) in the most endangered areas. Traps and "trap trees" could be also used as bark beetle control, but only in certain conditions. As we catch only a part of swarming beetle populations in pheromone traps and "trap trees", we cannot stop escalation of bark beetles only with these actions. Use of insecticides in Slovenia is limited by the Forest Act (1993), use of dangerous insecticides is also forbidden in FSC certified forests. Use of attested insecticides can be reasonably performed only in a limited scope for the immobilization of the infested forest wood assortments, which cannot be transported from forest before the flying out of a new beetle generation. Use of insecticide nets (for example systems Trinet(R) and Storanet(R)) is due to their negative impact on forest ecosystem not justifiable
Keywords: Picea abies; podlubniki; Ips typographus; Pityogenes chalcographus; Norway spruce; integralno varstvo gozdov; bark beetles; biotehniške metode; integrated forest protection; biotechnical methods; insekticidi; Slovenija; insecticides; navadna smreka; Slovenia